Lithium ion battery electrolyte, lithium ion battery and preparation method thereof
By using polyfluoro benzene and functional additives I and II in the lithium-ion battery electrolyte, a stable SEI protective film and interface layer is formed, which solves the problem of capacity attenuation and cycle life of lithium-ion batteries under high voltage conditions, and improves the cycling and high-temperature performance of the battery.
Patent Information
- Application Number
- CN202410419790.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-04-09
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2044-04-09
AI Technical Summary
Under high voltage conditions, the particles of the cathode material of the lithium-ion battery are fragile, and the electrolyte enters the inside of the cathode material, destroying the structure, resulting in the attenuation of the battery capacity, and the long cycle life cannot be guaranteed.
Using a lithium-ion battery electrolyte composed of polyfluoro benzene, electrolyte salt, functional additive I, and functional additive II, the Si ane in functional additive I can easily form a SEI protective film on the negative electrode, and the -C≡N and -O-functional groups in functional additive II improve the oxidation resistance of the electrolyte, form a stable LiF-rich interface layer, and optimize the negative electrode interface.
It improves the circulation performance and high temperature performance of lithium-ion batteries, extends the service life of the battery, and reduces the attenuation of battery capacity.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of lithium ion batteries, and in particular relates to a lithium ion battery electrolyte, a lithium ion battery and a preparation method thereof. Background Art
[0002] Lithium-ion battery is a rechargeable battery that mainly relies on the movement of lithium ions between the positive and negative electrodes to work. + Insertion and deinsertion back and forth between the two electrodes: During charging, Li + The electrolyte is then embedded in the negative electrode after being removed from the positive electrode, and the negative electrode is in a lithium-rich state; the opposite is true during discharge. Due to the advantages of high specific energy, no memory effect, long cycle life, and low self-discharge, lithium-ion batteries are widely used in digital, energy storage, electric vehicles and other fields.
[0003] With the improvement of people's living standards and their yearning for a better life, higher requirements are also put forward for battery energy density. In order to improve the battery energy density, it is necessary to further increase the limiting voltage of the positive electrode material. As the limiting voltage of the positive electrode material continues to increase, the gram capacity of the positive electrode material gradually increases, but the high temperature performance of the battery deteriorates seriously, and the long cycle life cannot be guaranteed. Especially under high voltage (4.5V), during long-term cycle charge and discharge, due to the fragmentation and shedding of the positive electrode material particles, the electrolyte enters the positive electrode material and destroys the structure of the positive electrode material. At the same time, the release of active oxygen further accelerates the oxidative decomposition of the electrolyte, and the protective film on the surface of the negative electrode will also be continuously damaged, eventually causing the problem of serious attenuation of the battery capacity. Summary of the invention
[0004] In view of the technical problems existing in the prior art, the object of the present invention is to provide a lithium ion battery electrolyte, the electrolyte is composed of an organic solvent, an electrolyte salt and a functional additive, the organic solvent contains polyfluorinated benzene; the functional additive includes functional additive I and functional additive II;
[0005] The functional additive I is of formula (1), and the additive II is of formula (2):
[0006]
[0007] wherein R1 to R4 are each independently selected from a hydrogen atom, a substituted or unsubstituted C1 to C6 alkyl group, a substituted or unsubstituted C1 to C6 unsaturated hydrocarbon group, a substituted or unsubstituted C2 to C 20 One of the groups formed by substitution of an alkenyl group, a cyano group, an aryl group having 6 to 18 carbon atoms with a carbonyl group, a cyano group, a halogen atom, a nitro group, a carboxyl group, and a sulfonic acid group, wherein the halogen atom is F, Cl, or Br;
[0008] The value range of n1 and n2 is 1 to 10 respectively;
[0009] The X is any one selected from C, N or B;
[0010] The mass of the additive I accounts for 0.2% to 3% of the total mass of the electrolyte;
[0011] The mass of the additive II accounts for 0.3% to 2.4% of the total mass of the electrolyte.
[0012] Furthermore, the polyfluorobenzene is selected from any one of Formulas 1-1 to 1-7:
[0013]
[0014] 1-7.
[0015] Furthermore, the functional additive I is selected from any one of formulas (1)-1 to (1)-8:
[0016]
[0017]
[0018] Furthermore, the functional additive II is selected from any one of formulas (2)-1 to (2)-5:
[0019]
[0020]
[0021] Furthermore, the electrolyte lithium salt is selected from one or more of lithium hexafluorophosphate (LiPF6), lithium difluorophosphate (LiPO2F2), lithium difluorooxalatoborate (LiDFOB), lithium bis(trifluoromethylsulfonyl imide), lithium difluorobis(oxalatophosphate), lithium tetrafluoroborate, lithium bis(oxalatoborate), lithium hexafluoroantimonate, lithium hexafluoroarsenate, lithium bis(trifluoromethylsulfonyl)imide, lithium bis(pentafluoroethylsulfonyl)imide, tris(trifluoromethylsulfonyl)methyl lithium or lithium bis(trifluoromethylsulfonyl)imide.
[0022] Furthermore, the mass of the lithium salt accounts for 5-25% of the total mass of the electrolyte.
[0023] Further, the organic solvent also includes carbonate and / or carboxylate, and the carbonate is selected from one or more of the following solvents: ethylene carbonate (EC), propylene carbonate (PC), dimethyl carbonate, diethyl carbonate (DEC), ethyl methyl carbonate;
[0024] The carboxylic acid ester is selected from one or more of the following solvents: propyl acetate, n-butyl acetate, isobutyl acetate, n-pentyl acetate, isopentyl acetate, propyl propionate (PP), ethyl propionate (EP), methyl butyrate, and ethyl butyrate.
[0025] The present invention also has another object to provide a lithium ion battery, the battery comprising a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte;
[0026] The electrolyte is the electrolyte described above;
[0027] The positive electrode sheet comprises a current collector and a positive electrode active material layer coated on one side or both sides of the positive electrode current collector, wherein the positive electrode active material layer comprises a positive electrode active material, a conductive agent and a binder;
[0028] The negative electrode sheet comprises a current collector and a negative electrode active material layer coated on one side or both sides of the negative electrode current collector, wherein the negative electrode active material layer comprises a negative electrode active material, a conductive agent and a binder;
[0029] The mass percentage of each component in the positive electrode active material layer is: 80-99.8wt% of positive electrode active material, 0.1-10wt% of conductive agent, and 0.1-10wt% of binder;
[0030] The mass percentage of each component in the positive electrode active material layer is: 90-99.6wt% of positive electrode active material, 0.2-5wt% of conductive agent, and 0.2-5wt% of binder;
[0031] The mass percentage of each component in the negative electrode active material layer is: 80-99.8wt% of negative electrode active material, 0.1-10wt% of conductive agent, and 0.1-10wt% of binder;
[0032] The mass percentage of each component in the negative electrode active material layer is: 90-99.6wt% of negative electrode active material, 0.2-5wt% of conductive agent, and 0.2-5wt% of binder;
[0033] The conductive agent is selected from at least one of conductive carbon black, acetylene black, Ketjen black, conductive graphite, conductive carbon fiber, carbon nanotubes, metal powder, and carbon fiber.
[0034] The binder is selected from at least one of sodium carboxymethyl cellulose, styrene-butadiene latex, polytetrafluoroethylene and polyethylene oxide.
[0035] The negative electrode active material is artificial graphite.
[0036] The carbon-based negative electrode material includes at least one of artificial graphite, natural graphite, mesophase carbon microbeads, hard carbon, and soft carbon.
[0037] The positive electrode active material is selected from one or more of lithium iron phosphate and lithium manganese oxide.
[0038] The third object of the present invention is to provide a method for preparing a lithium-ion battery, the method comprising the following steps: stacking the positive electrode sheet, the negative electrode sheet and the isolation membrane in the order of the positive electrode sheet, the isolation membrane and the negative electrode sheet, and then winding to obtain a battery cell; placing the battery cell in an outer packaging aluminum foil, injecting an electrolyte into the outer packaging, and obtaining a lithium-ion battery through vacuum packaging, standing, forming, shaping, sorting and other processes.
[0039] The present invention also has the following beneficial effects:
[0040] 1. In the present invention, additives I and additives II are used as electrolyte additives for lithium ion batteries. Under the synergistic effect of additives I and additives II, the Si alkane in additive I easily forms an SEI protective film at the negative electrode, and the five-membered ring forms an interface film at the outer layer of the positive electrode, which has good high temperature resistance and low impedance, is conducive to the migration of lithium ions, and thus improves the cycle performance of the battery.
[0041] 2. In the present invention, after the additive I easily forms a protective film, the -C≡N and -O- functional groups contained in the additive II have a higher oxidation potential, which greatly improves the oxidation resistance of the electrolyte under high voltage. In addition, the organic solvent in the electrolyte also contains polyfluorobenzene with more -F functional groups, which can effectively improve the reduction potential of the additive, so that it forms a stable LiF-rich interface layer on the negative electrode surface, optimizes the negative electrode interface, and enables the -C≡N functional group contained in the additive II to combine with the transition metal ions on the negative electrode surface and participate in the formation of the SEI film, thereby inhibiting the deposition of the transition metal ions dissolved from the positive electrode at the negative electrode, reducing the adverse effects of the second additive on the SEI interface, and improving the incompatibility of the second additive with graphite or lithium metal negative electrodes. Therefore, the synergistic cooperation of additives I and II, and the solvent polyfluorobenzene improves the comprehensive performance of the battery. DETAILED DESCRIPTION
[0042] The following is a specific and detailed description of an embodiment of the present invention. This embodiment is implemented on the premise of the technical solution of the present invention, and a detailed implementation method and a specific operation process are given. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be regarded as the scope of protection of the present invention.
[0043] The lithium ion battery of the present invention comprises a negative electrode sheet, an electrolyte, a positive electrode sheet, a separator and an outer package. The positive electrode sheet, the separator and the negative electrode sheet are stacked to obtain a battery core or the positive electrode sheet, the separator and the negative electrode sheet are stacked and then wound to obtain a battery core, the battery core is placed in an outer package, and the electrolyte is injected into the outer package to obtain the lithium ion battery of the present invention:
[0044] The lithium ion batteries of Examples 1 to 10 and Comparative Examples 1 to 2 are prepared by the following steps:
[0045] Cathode sheet preparation
[0046] The positive electrode active materials lithium cobalt oxide (LiCoO2), polyvinylidene fluoride (PVDF), SP (super P) and carbon nanotubes (CNT) are mixed in a mass ratio of 96:2:1.5:0.5, N-methylpyrrolidone (NMP) is added, and the mixture is stirred under the action of a vacuum mixer until the mixed system becomes a positive electrode active slurry with uniform fluidity; the positive electrode active slurry is evenly coated on both surfaces of an aluminum foil; the coated aluminum foil is dried, and then rolled and cut to obtain the desired positive electrode sheet.
[0047] Negative electrode preparation
[0048] The negative electrode active materials artificial graphite, silicon oxide, sodium carboxymethyl cellulose (CMC-Na), styrene-butadiene rubber, conductive carbon black (SP) and single-walled carbon nanotubes (SWCNTs) are mixed in a mass ratio of 79.5:15:2.5:1.5:1:0.5, deionized water is added, and the negative electrode active slurry is obtained under the action of a vacuum mixer; the negative electrode active slurry is evenly coated on both surfaces of the copper foil; the coated copper foil is dried at room temperature, and then transferred to an oven at 80°C for drying for 10 hours, and then cold pressed and cut to obtain the negative electrode sheet.
[0049] Preparation of electrolyte
[0050] In a glove box filled with argon (H2O < 0.1ppm, O2 < 0.1ppm), EC / PC / DEC / PP were mixed evenly in a mass ratio of 10 / 20 / 40 / 30, and then 1 mol / L of fully dried lithium hexafluorophosphate (LiPF6) was quickly added thereto. After dissolution, 9 wt% of fluoroethylene carbonate based on the total mass of the electrolyte, 4 wt% of 1,3-propane sultone (PS) based on the total mass of the electrolyte, 3 wt% of 1,3,6-hexanetrinitrile (HTCN) based on the total mass of the electrolyte, and additives I, additives II and polyfluorobenzene as shown in structural formula 1-4, the specific electrolyte formula is shown in Table 1, stirred evenly, and after passing the moisture and free acid tests, the desired electrolyte was obtained.
[0051] The preparation of lithium-ion batteries will be steps
[0052] The positive electrode sheet, the negative electrode sheet and the separator are stacked in the order of the positive electrode sheet, the separator and the negative electrode sheet, and then wound to obtain a battery cell; the battery cell is placed in an outer packaging aluminum foil, the electrolyte of step 3) is injected into the outer packaging, and a lithium ion battery is obtained through vacuum packaging, standing, forming, shaping, sorting and other processes. The battery of the present invention has a charge and discharge range of 3.0 to 4.45V.
[0053] Table 1. Composition of electrolyte additives in lithium ion batteries of comparative examples and embodiments:
[0054]
[0055] The lithium ion batteries obtained in Examples 1 to 10 and Comparative Examples 1 to 2 were subjected to the following performance tests, respectively:
[0056] Performance Test:
[0057] (1) 25℃ Cyclic Performance Test
[0058] The battery in Table 1 was charged and discharged at 25°C at a rate of 1C within the charge and discharge cut-off voltage range. The discharge capacity in the first week of the test was calculated as x1mAh, and the discharge capacity in the Nth week was calculated as y1mAh. The capacity in the Nth week was divided by the capacity in the first week to obtain the cycle capacity retention rate R1=y1 / x1 in the Nth week.
[0059] (2) 45℃ Cyclic Performance Test
[0060] The battery in Table 1 was charged and discharged at 45°C at a rate of 1C within the charge and discharge cut-off voltage range. The discharge capacity in the first week of the test was x2mAh, and the discharge capacity in the Nth week was y2mAh. The capacity in the Nth week was divided by the capacity in the first week to obtain the cycle capacity retention rate R2=y2 / x2 in the Nth week.
[0061] Table 2. Performance test results:
[0062]
[0063]
[0064] It can be seen from Table 2 that when the embodiments and comparative examples are subjected to cycle performance tests for different numbers of weeks, the combination of Additive I and Additive II can significantly improve the 25°C room temperature cycle performance and 45°C high temperature cycle performance of the battery.
Claims
1. A lithium ion battery electrolyte, characterized in that: The electrolyte is composed of an organic solvent, an electrolyte lithium salt and a functional additive, wherein the organic solvent contains polyfluorinated benzene; the functional additive includes a functional additive I and a functional additive II; The mass of the additive I accounts for 0.2% to 3% of the total mass of the electrolyte, and the mass of the additive II accounts for 0.3% to 2.4% of the total mass of the electrolyte; The polyfluorobenzene is selected from any one of formulas 1-2 to 1-7: The functional additive I is selected from any one of the following: The functional additive II is selected from any one of formulas (2)-1 to (2)-5:
2. The electrolyte according to claim 1, characterized in that The electrolyte lithium salt is selected from one or more of lithium hexafluorophosphate, lithium difluorophosphate, lithium difluorooxalatoborate, lithium bis(trifluoromethylsulfonyl)imide, lithium difluorobis(oxalatophosphate), lithium tetrafluoroborate, lithium bis(oxalatoborate), lithium hexafluoroantimonate, lithium hexafluoroarsenate or lithium bis(pentafluoroethylsulfonyl)imide.
3. The electrolyte according to claim 2, characterized in that The mass of the electrolyte lithium salt accounts for 5-25% of the total mass of the electrolyte.
4. The electrolyte according to claim 1, characterized in that The organic solvent also includes carbonate, and / or carboxylate; The carbonate is selected from one or more of the following solvents: ethylene carbonate, propylene carbonate, dimethyl carbonate, diethyl carbonate, and ethyl methyl carbonate.
5. The electrolyte according to claim 4, characterized in that The carboxylic acid ester is selected from one or more of the following solvents: propyl acetate, n-butyl acetate, isobutyl acetate, n-pentyl acetate, isopentyl acetate, propyl propionate, ethyl propionate, methyl butyrate, and ethyl butyrate.
6. A lithium ion battery, characterized in that: The battery comprises a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte; The electrolyte is selected from the electrolyte of any one of claims 1 to 5; The positive electrode sheet comprises a current collector and a positive electrode active material layer coated on one side or both sides of the positive electrode current collector, wherein the positive electrode active material layer comprises a positive electrode active material, a conductive agent and a binder; The negative electrode sheet comprises a current collector and a negative electrode active material layer coated on one side or both sides of the negative electrode current collector, wherein the negative electrode active material layer comprises a negative electrode active material, a conductive agent and a binder.
7. The lithium-ion battery according to claim 6, characterized in that: The conductive agent is selected from at least one of acetylene black, Ketjen black, conductive graphite, carbon nanotubes, metal powder, and carbon fiber.
8. The lithium-ion battery according to claim 6, characterized in that: The binder is selected from at least one of sodium carboxymethyl cellulose, styrene-butadiene latex, polytetrafluoroethylene and polyethylene oxide.
9. The lithium-ion battery according to claim 6, characterized in that: The negative electrode active material is artificial graphite.
10. The lithium ion battery according to claim 6, characterized in that: The positive electrode active material is selected from one or more of lithium iron phosphate and lithium manganese oxide.
11. The method for preparing a lithium ion battery according to any one of claims 6 to 10, characterized in that: The method comprises: The positive electrode sheet, the negative electrode sheet and the separator are stacked in the order of the positive electrode sheet, the separator and the negative electrode sheet, and then wound to obtain a battery cell; The battery cell is placed in an outer packaging aluminum foil, the electrolyte is injected into the outer packaging, and the lithium-ion battery is obtained through vacuum packaging, standing, forming, shaping, and sorting processes.
Citation Information
Patent Citations
High-temperature-resistant electrolyte, secondary battery and application thereof
CN115425292A
Electrolyte and lithium ion battery
CN116072965A
Non-aqueous electrolyte and lithium ion battery
CN116706236A
Electrolyte and preparation method and application thereof
CN117558980A
Electrolyte additive for secondary battery, manufacturing method thereof, electrolyte, and secondary battery comprising the same
KR1020220124963A